Faktor-Faktor yang Mempengaruhi Produksi Jagung di Desa Kayu Gadang Menggunakan Analisis Regresi Linier Berganda - Ceng Sri Yunita; Helma Helma; Minora Longgom Nasution (Journal of Mathematics UNP, 2021)
Abstract –The village of Kayu Gadang is one of the villages in the subdistrict of South PesisirRegency silk economy society resting on farming corn. But the community does not yet have enough information about the factors that affect corn production such as land area, the distance to the source of the water, the land length of the trunks, width and fertilizer so that cause less productive corn production results obtained community which is around 602,549 tonnes by 2015 that should more than 605,352 tons in 2014. Based on the above issues, then the formulation of the problem in this research are factors that affect the production of any corn in the village of Kayu Gadang SouthPesisirRegency. The purpose of this research is to know what a linear multiple regression model and the factors that affect the production of maize in the village of Kayu Gadang South Pesisir Regency. Keywords  –kayu gadang, the production of corn, multiple linear regression analysis